2020
DOI: 10.1155/2020/5896016
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness in Myopia: An OCT-Based Study in Young Chinese Patients

Abstract: Myopia is a common cause of visual impairment worldwide. Choroidal thickness (ChT) reflects the characteristic changes in myopic children and may be used as an important index of myopia. The purpose of this study was to investigate ChT and its distribution across the posterior pole in young myopic Chinese patients using enhanced depth imaging optical coherence tomography (EDI-OCT) and to explore the factors associated with it. A total of 402 myopic Chinese patients aged 6–16 years who underwent complete ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
(85 reference statements)
0
12
2
Order By: Relevance
“…However, it is likely that shorter axial lengths result from choroidal thickening and longer axial lengths from choroidal thinning. 25,[27][28][29]…”
mentioning
confidence: 99%
“…However, it is likely that shorter axial lengths result from choroidal thickening and longer axial lengths from choroidal thinning. 25,[27][28][29]…”
mentioning
confidence: 99%
“…We measured the average subfoveal Cht of both eyes using built-in software, with the LE and the RE being 223 μm and 224 μm, respectively. However, in an OCT-based study of myopia in Chinese youth, the mean subfoveal Cht was 303.08 ± 76.87 μm [ 11 ], and it could be distinguished from the OCT image that it resulted from atrophy of the choriocapillaris layer. Prior research also demonstrated that the choroidal vascularity index, which reflects middle and large choroidal vascularity, has recently shown a downward trend in PR eyes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that, in normal physiological development, the choroid becomes thicker and the ocular axis extends [ 26 , 27 ]. When myopia is imminent, the choroidal thickness would become thinner [ 17 , 28 ] and is characterized by continuously thinning choroids in patients with progressive myopia. [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (ZEISS CIRRUS HD-OCT-5000) was used to measure the ChT of the subjects; the head position was fixed during the whole measurement. The “HD CROSS” test method and Enhanced Deep Imaging (EDI) mode were selected for standardized measurements [ 10 , 17 ].…”
Section: Methodsmentioning
confidence: 99%